Associations between urine phthalate metabolites and thyroid function in pregnant women and the influence of iodine status. (April 2020) - Villanger, Gro D.; Drover, Samantha S.M.; Nethery, Rachel C.; Thomsen, Cathrine; Sakhi, Amrit K.; Øvergaard, Kristin R.; Zeiner, Pal; Hoppin, Jane A.; Reichborn-Kjennerud, Ted; Aase, Heidi; Engel, Stephanie M.
Highlights: We investigated the relations between phthalates and thyroid function mid-pregnancy. We accounted for the urinary phthalate metabolite mixture by factor analyses. We found relationships between phthalate factors and thyroid function, mainly T3. Dietary iodine intake in pregnancy influenced some of these relationships. Abstract: Background: Human populations, including susceptible subpopulations such as pregnant women and their fetuses, are continuously exposed to phthalates. Phthalates may affect the thyroid hormone system, causing concern for pregnancy health, birth outcomes and child development. Few studies have investigated the joint effect of phthalates on thyroid function in pregnant women, although they are present as a mixture with highly inter-correlated compounds. Additionally, no studies have investigated if the key nutrient for thyroid health, iodine, modifies these relationships. Methods: In this study, we examined the cross-sectional relationships between concentrations of 12 urinary phthalate metabolites and 6 plasma thyroid function biomarkers measured mid-pregnancy ( 17 week gestation) in pregnant women (N = 1072), that were selected from a population-based prospective birth cohort, The Norwegian Mother, Father and Child Cohort study (MoBa). We investigated if the phthalate metabolite-thyroid function biomarker associations differed by iodine status by using a validated estimate of habitual dietary iodine intake based on a food frequency questionnaire from the 22nd gestation week. We accounted for the phthalate metabolite mixture by factor analyses, ultimately reducing the exposure into two uncorrelated factors. These factors were used as predictors in multivariable adjusted linear regression models with thyroid function biomarkers as the outcomes. Results: Factor 1, which included high loadings for mono- iso -butyl phthalate (MiBP), mono-n-butyl phthalate (MnBP), and monobenzyl phthalate (MBzP), was associated with increased total triiodothyronine (TT3) and free T3 index (fT3i). These associations appeared to be driven primarily by women with low iodine intake (<150 µg/day, 70% of our sample). Iodine intake significantly modified ( p -interaction < 0.05) the association of factor 1 with thyroid stimulating hormone (TSH), total thyroxine (TT4) and free T4 index (fT4i), such that only among women in the high iodine intake category (≥150 µg/day, i.e. sufficient) was this factor associated with increased TSH and decreased TT4 and FT4i, respectively. In contrast, factor 2, which included high loadings for di-2-ethylhexyl phthalate metabolites (∑DEHP) and di- iso -nonyl phthalate metabolites (∑DiNP), was associated with a decrease in TT3 and fT3i, which appeared fairly uniform across iodine intake categories. Conclusion: We find that phthalate exposure is associated with thyroid function in mid-pregnancy among Norwegian women, and that iodine intake, which is essential for thyroid health, could influence some of these relationships.